Ontology for the Domain of Food Science - Padmavathi, T.; Krishnamurthy, M. (Journal of Information and Knowledge, 2016)
Information in the domain of food science is vast and techniques for managing and organizing such knowledge become essential. Present day information retrieval systems are based on full text searching for keywords which often retrieves irrelevant information and does not fulfill the user's requirements. A solution to the above chaos is ontology. The current paper describes an ontology for food science domain using Protege.